Review paperHigh-dose-rate intraoperative radiation therapy: the nuts and bolts of starting a program - Moningi, Shalini; Armour, Elwood P.; Terezakis, Stephanie A.; Efron, Jonathan E.; Gearhart, Susan L.; Bivalacqua, Trinity J.; Le, Yi; Kien, Sook; Wolfgang, Christopher L.; Zellars, Richard C.; Ellsworth, Susannah G.; Ahuja, Nita; et al. (Journal of Contemporary Brachytherapy, 2014)
High-dose-rate intraoperative radiation therapy (HDR-IORT) has historically provided effective local control (LC) for patients with unresectable and recurrent tumors. However, IORT is limited to only a few specialized institutions and it can be difficult to initiate an HDR-IORT program. Herein, we provide a brief overview on how to initiate and implement an HDR-IORT program for a selected group of patients with gastrointestinal and pelvic solid tumors using a multidisciplinary approach. Proper administration of HDR-IORT requires institutional support and a joint effort among physics staff, oncologists, surgeons, anesthesiologists, and nurses. In order to determine the true efficacy of IORT for various malignancies, collaboration among institutions with established IORT programs is needed.